2009
DOI: 10.1021/ac900063u
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Melamine in Milk Products by Surface Desorption Atmospheric Pressure Chemical Ionization Mass Spectrometry

Abstract: Without any sample pretreatment, trace amounts of melamine in various milk products were rapidly detected noting the characteristic fragments (i.e., m/z 110, 85, and 60) in the MS/MS spectrum of protonated melamine molecules (m/z 127) recorded by using surface desorption atmospheric pressure chemical ionization mass spectrometry. Signal responses of the most abundant ionic fragment (m/z 85) of protonated melamine were well correlated with the amounts of melaime in milk products, showing a dynamic range about 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(173 citation statements)
references
References 52 publications
6
165
1
1
Order By: Relevance
“…Several authors have proposed the direct analysis of MM in milk or pet food using various analytical methodologies. [15][16][17][18][19][20] The LOD for MM in the present study, after considering the 10-fold dilution of the samples, was rather low when compared with those from studies that did not involve prior sample preparation. Rambla-Alegre et al reported a direct injection method for the analysis of MM using HPLC-UV; they obtained an LOD (5 ppb) similar to ours.…”
Section: Analytical Performancecontrasting
confidence: 58%
See 1 more Smart Citation
“…Several authors have proposed the direct analysis of MM in milk or pet food using various analytical methodologies. [15][16][17][18][19][20] The LOD for MM in the present study, after considering the 10-fold dilution of the samples, was rather low when compared with those from studies that did not involve prior sample preparation. Rambla-Alegre et al reported a direct injection method for the analysis of MM using HPLC-UV; they obtained an LOD (5 ppb) similar to ours.…”
Section: Analytical Performancecontrasting
confidence: 58%
“…[15][16][17][18][19][20] These methods include HPLC-UV, 15 Raman spectroscopy 16 direct-analysis-in-real-time mass spectrometry (DART-MS), 17 ultrasound-assisted extractive electrospray ionization mass spectroscopy (EESI-MS), 18 surface desorption atmospheric pressure chemical ionization mass spectrometry (DAPCI-MS), 19 and low-temperature plasma/tandem mass spectrometry (LTP-MS-MS). 20 Notably, most of the instruments used in these methodologies are very expensive; in addition, the limits of detection (LODs) of these methods are variable because of the intense noise caused by the matrix.…”
mentioning
confidence: 99%
“…Currently, various methods-including thin-layer chromatography [6], gas chromatography (GC) [7,8], high-performance liquid chromatography [9][10][11][12], enzyme-linked immunosorbent assay technology [13], matrix-assisted laser desorption/ ionization mass spectrometry (MALDI-MS) [14], and surface desorption atmospheric pressure chemical ionization mass spectrometry [15]-have been used to detect melamine in food. However, these methods usually suffer from drawbacks, such as the need for a complicated sample preparation process, clean-up steps, and a time-consuming determination process, so they cannot fulfill the requirement for fast in situ detection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, breakthrough of mass [36,37]. After DESI, more than 20 ambient ionization techniques were further developed, including direct analysis in real time (DART) [38,39], surface desorption atmospheric pressure chemical ionization (DAPCI) [40,41], extractive electrospray ionization (EESI) [42], low temperature plasma (LTP) [43,44], and easy ambient sonic ionization (EASI) [45]. Two major advantages of ambient mass spectrometry are minimal sample pre-treatment and high-throughput MS analysis [46][47][48].…”
Section: Introductionmentioning
confidence: 99%